2-Aminobenzoxazole-appended coumarins as potent and selective inhibitors of tumour-associated carbonic anhydrases. (1st January 2022) - Fuentes-Aguilar, Alma; Merino-Montiel, Penélope; Montiel-Smith, Sara; Meza-Reyes, Socorro; Vega-Báez, José Luis; Puerta, Adrián; Fernandes, Miguel X.; Padrón, José M.; Petreni, Andrea; Nocentini, Alessio; Supuran, Claudiu T.; López, Óscar; et al.
Abstract: We have carried out the design, synthesis, and evaluation of a small library of 2-aminobenzoxazole-appended coumarins as novel inhibitors of tumour-related CAs IX and XII. Substituents on C-3 and/or C-4 positions of the coumarin scaffold, and on the benzoxazole moiety, together with the length of the linker connecting both units were modified to obtain useful structure-activity relationships. CA inhibition studies revealed a good selectivity towards tumour-associated CAs IX and XII ( K i within the mid-nanomolar range in most of the cases) in comparison with CAs I, II, IV, and VII ( K i > 10 µM); CA IX was found to be slightly more sensitive towards structural changes. Docking calculations suggested that the coumarin scaffold might act as a prodrug, binding to the CAs in its hydrolysed form, which is in turn obtained due to the esterase activity of CAs. An increase of the tether length and of the substituents steric hindrance was found to be detrimental to in vitro antiproliferative activities. Incorporation of a chlorine atom on C-3 of the coumarin moiety achieved the strongest antiproliferative agent, with activities within the low micromolar range for the panel of tumour cell lines tested. Graphical Abstract: UF0001